Education Student Perceptions and Primary Teacher Preparedness to Teach Design and Technology in a Western Australian Context - Pagram, J.; Cooper, Martin (2017)
School education systems in Australia are very local varying between the six states and two mainland territories. Each State and Territory government runs education at this level. Australia now has (for the first time) a new National Curriculum in which Design and Technology runs from K to year 10. This paper examines the perceptions of Design and Technology of pre-service teachers in this area in Western Australia (WA). The data was gathered at Edith Cowan University in Perth, the only university to train Design and Technology teachers in WA. The number of students studying Design and Technology (D&T) education at Edith Cowan University (ECU) in WA has fallen over the past few years. This is despite an increasing shortfall in the workplace leading to many graduate job opportunities. In addition primary teachers are now expected to teach design and technology in their classes and the researchers wondered how much preparation they receive in their training. In the context of these problems the researchers set out to examine the perceptions of existing ECU School of Education students towards D&T to determine if preconceived views relating to the area of D&T were discouraging study in the area. Two online surveys were developed and delivered via the Qualtrics (Qualtrics, Provo, UT) commercial survey engine. Amongst the findings is a clear indication that before entering university many students’ views towards design and technology are biased and stereotyped based upon school experiences. In particular the perception is that, while seen as creative, design and technology is about men making things. For those training to be primary teachers, just over half of respondents felt comfortable teaching D&T while most had either no formal training in D&T, or half an online unit during their course. This paper discusses these findings and their implications.